Depósitos flúvio-costeiros da Formação Raizama, Ediacarano-Cambriano da faixa Paraguai Norte, região de Nobres, Mato Grosso, Brasil - SANTOS, Hudson Pereira (2015)
The Ediacaran-Cambrian Raizama Formation presents siliciclastic deposits exposed discontinuously along of the southern margin of the Amazon Craton and the Northern Paraguay Belt, Central-Western Brazil. These deposits are interpreted as progradational coastal succession conformably overling the carbonate platform succession of the Upper Araras Group. The facies and stratigraphic analysis of outcrop section were carried out in the Nobres region, State of Mato Grosso, allowed the individualization of seventeen facies, grouped into five facies associations (FA): FA1) lower shoreface, consisting of sandstone with parallel and wave-truncated lamination (microhummocky) parted by laminated mudstones, locally bioturbed by Skolithos; FA2) upper shoreface, composed by parallel and swaley cross bedded sandstone; FA3) subtidal, represented by sandstones with tangential and through cross stratifications drapped by siltstone/very fine sandstone laminae interpreted as channel and bar deposits; FA4) tidal flat is characterized by sandstones with tangential and sigmoidal cross bedding, even parallel stratification, low-angle cross bedding, mud cracks, siltstone/very fine sandstone rhythmites with flaser bedding, organized in shallowing-meter scale cycles; and FA5) distal braid plain consisting of sandstones with through cross-bedding and laterally discontinuous lags, parallel stratification and low-angle cross stratification partially reworked by wave. The sedimentation of the Raizama Formation suggests an increase in the siliciclastic supply linked to uplift regions of the Craton in the northwest of the studied area, succeeding the Araras carbonate platform deposits. Tubular trace fossils in the FA1 indicate, by the first time, the presence of burrowed organisms, what strongly points to an age near of the Ediacaran-Cambrian boundary.